1999
DOI: 10.1108/13620439910249962
|View full text |Cite
|
Sign up to set email alerts
|

Careers in Ethiopia: an exploration of careerists’ perceptions and strategies

Abstract: Examines the small but growing literature placing career related behaviours and practices within their national context and outlines a Western framework of career strategies. Identifies some of the key economic, social and political developments in Ethiopia's recent history and presents and discusses data from a survey of Ethiopian careerists which explores factors influencing career decisions, levels of (and reasons for) career optimism/ pessimism, and career strategies employed. Data from a previous study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…They emphasize that this process is defined by the fundamental beliefs of the person and the selected career path and job are based on early experiences in the family and life at school. National culture is what shapes the filters that ensure individuals perceive the business worldexternal career-in the same manner as others that view the world through the same cultural lens as the person (Counsell, 1999). In addition to the cultural differences stated the social, economic and political structures could also have an effect on the career choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They emphasize that this process is defined by the fundamental beliefs of the person and the selected career path and job are based on early experiences in the family and life at school. National culture is what shapes the filters that ensure individuals perceive the business worldexternal career-in the same manner as others that view the world through the same cultural lens as the person (Counsell, 1999). In addition to the cultural differences stated the social, economic and political structures could also have an effect on the career choices.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that examine the effects of personal and environmental discovery on the career choices of the individual (Gianakos, 1999;Junk and Armstrong, 2010;Nazli, 2007;Ng, Burke and Fiksenbaum, 2008). In resources pertaining to the choice of career, it is possible to see studies examining the effects of the culture a person is embroiled in on his/her career choices (Ayala and Oshrit, 2008;Counsell, 1999;Derr and Laurent, 1989;Leong, Hardin and Gupta, 2010;Thomas and Inkson, 2007;Vigoda-Gadot and Grimland, 2008).…”
mentioning
confidence: 99%
“…A key distinction in Counsell's (1999) and Counsell and Popova's (2000) research is that they identified the 'economic and political situation' as the most frequently mentioned influence on career-related decisions, whereas Counsell's 1996 study identified 'information and advice from parents and close family' as the most frequently mentioned influence. Previous research findings from other authors also suggest that people and situational factors play important roles in students' perceptions when a field of study and career choice are considered (Swanson and Tokar, 1991;Ackerman and Gross 2006).…”
Section: Career Decisionsmentioning
confidence: 99%
“…The above literature review shows that various studies have investigated career goals and the importance of factors influencing students' career decision making (Swanson and Tokar, 1991;Counsell, 1999, Counsell andPopova, 2000;Orndorff, 2002;Sosik et al, 2004;Myburgh, 2005;Ackerman and Gross 2006;Hussain et al, 2007). Findings from several international studies have identified differences between gender groups in career goals and in influential factors in career decision making (Counsell, 1996;Le, 1999;Delmar and Davidsson, 2000;Van Praag, 2003;Piotrowski and Cox, 2004).…”
Section: Research Objectivesmentioning
confidence: 99%
“…Harrington (1986) reported on the crosscultural applicability of Holland's theory of vocational development and the career decision making system, by studying the results of translating this model into Spanish and French and adapting it for use in Canada. Two other studies (Counsell, 1999;Counsell & Popova, 2000) considered the contextual factors influencing careers decision making in Ethiopia and Bulgaria respectively. These studies of decision-making and strategies in a national context drew attention to additional careers strategies adopted by workers in these countries such as politics, ethnic/ tribal affiliations or corruption.…”
mentioning
confidence: 99%